Activation of the Economic Security of Ukraine in Terms of the European Integration - Andrii Kubaienko (Montenegrin Journal of Economics)
The full-fledged involvement of Ukraine into the European association stipulates the creation and adherence to the terms so to reinforce the economic and commercial relations promoting the gradual integration of the national economy into the European market. The presence of significant regional disproportions in the social and economic growth in Ukraine requires differentiated approaches in working out measures of regional development designated to assist in creating a free trade area and reinforcing the economic and sectoral collaboration of Ukraine and the EU. So, there arises a need of monitoring and estimation of the economic reform progress in the regions of Ukraine in terms of the European Integration processes aimed to establish strong and weak sides, to substantiate priorities and measures of their achievement and an opportunity of their due correction in order to increase the ability of a region to work in the area of the European Integration. In order to implement the purpose of the research, it is reasonable above all to measure the integral value – European Integration Progress Index (Ір). From the most general standpoint, the index is a relative value designated to play the role of a generalised measure of a particular phenomenon formed under the influence of various components that cannot be directly summarised.